Physical activity, diet and quality of life during mandatory (COVID-19) quarantine following repatriation - Gradidge, Philippe Jean-Luc (SAGE Open Med Case Rep, 2020)
The coronavirus disease 2019 crisis in South Africa has been managed through an effective evidence-based approach. The aim of this case report was to determine the value of staying physically active during the coronavirus disease 2019 pandemic, using online resources to prevent the harmful effects of sedentary behaviour under confined living conditions. A repatriated South African citizen was placed into monitored 14-day quarantine confined to a room, self-monitoring dietary intake and physical and health measures, while engaged in online exercise videos and indoor walking. This study demonstrates that structured indoor activity improves physical and mental health outcomes, despite prolonged sitting time during the day. During the current pandemic and in the presence of limited freedom of movement, sustained physical activity is made feasible by accessing online tools and resources, essentially reducing vulnerability to existing cardiovascular health concerns. However, these findings are based on a single participant and therefore further study is required.